Findings of the Association for Computational Linguistics: ACL-IJCNLP 2021 2021
DOI: 10.18653/v1/2021.findings-acl.61
|View full text |Cite
|
Sign up to set email alerts
|

On Commonsense Cues in BERT for Solving Commonsense Tasks

Abstract: BERT has been used for solving commonsense tasks such as CommonsenseQA. While prior research has found that BERT does contain commonsense information to some extent, there has been work showing that pre-trained models can rely on spurious associations (e.g., data bias) rather than key cues in solving sentiment classification and other problems. We quantitatively investigate the presence of structural commonsense cues in BERT when solving commonsense tasks, and the importance of such cues for the model predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…There is a wide variety of datasets constructed to facilitate the development of novel approaches to the problem of NLI (Storks et al, 2019). The task has evolved within a series of RTE challenges (Dagan et al, 2005) and now comprises several standardized benchmark datasets such as SICK (Marelli et al, 2014), SNLI (Bowman et al, 2015), MNLI (Williams et al, 2018), and XNLI (Conneau et al, 2018b). Despite the rapid progress, recent work has found that these benchmarks may contain biases and annotation artifacts which raise questions whether state-of-the-art models indeed have or acquire the inference abilities (Tsuchiya 2018;Belinkov et al, 2019).…”
Section: Related Work Nli and Diagnostic Datasetsmentioning
confidence: 99%
“…There is a wide variety of datasets constructed to facilitate the development of novel approaches to the problem of NLI (Storks et al, 2019). The task has evolved within a series of RTE challenges (Dagan et al, 2005) and now comprises several standardized benchmark datasets such as SICK (Marelli et al, 2014), SNLI (Bowman et al, 2015), MNLI (Williams et al, 2018), and XNLI (Conneau et al, 2018b). Despite the rapid progress, recent work has found that these benchmarks may contain biases and annotation artifacts which raise questions whether state-of-the-art models indeed have or acquire the inference abilities (Tsuchiya 2018;Belinkov et al, 2019).…”
Section: Related Work Nli and Diagnostic Datasetsmentioning
confidence: 99%
“…Commonsense reasoning is the ability to reason about the underlying nature of situations humans encounter on a day-to-day basis such as the effects of Newtonian physics and the intentions of others. LMs are shown to possess a certain amount of commonsense knowledge in their parameters (Petroni et al, 2019;Davison et al, 2019;Cui et al, 2021). As a result, Huang et al (2019); Talmor et al (2019); Sap et al (2019); West et al (2021) introduce datasets to evaluate the extent to which LMs can reason over the knowledge they learned during pretraining.…”
Section: Commonsense Reasoningmentioning
confidence: 99%
“…In the past few years, large pre-trained language models (PLMs) have achieved state-of-the-art performance on many natural language processing tasks (Devlin et al, 2018;Liu et al, 2019b). Recent studies suggest that PLMs have possessed various kinds of knowledge into contextual representations (Goldberg, 2019;Petroni et al, 2019;Lin et al, 2019;Cui et al, 2021). However, the ability of PLMs to interpret similes remains under-explored.…”
Section: Introductionmentioning
confidence: 99%